CLEANED-R (Comprehensive Livestock Environmental Assessment for Improved Nutrition, a Secured Environment and Sustainable Development along Livestock and Fish Value Chains) tool - CGIAR Research Program on Livestock (2018)
The ReSLess project has parameterized the CLEANED tool at landscape scale for 3 study areas (Bama, Burkina Faso; Lushoto, Tanzania; Atsbi, Ethiopia). These tools have been used in a learning space along with a game aiming at stakeholders exploring possible livestock futures and negotiating the best alternatives for their area.